2010
DOI: 10.1111/j.1475-1313.2010.00775.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of chromatic sensitivity in AMD and diabetes: a comparative study

Abstract: These findings suggest that accurate measurements of RG and YB colour thresholds can provide a sensitive measure of functional change in diseases of the retina with patterns of loss that differ significantly in AMD and diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 49 publications
3
50
0
Order By: Relevance
“…Although several studies have shown that color vision deteriorates with advancing age [23,24], some controversy remains as to whether normal aging affects more the YB mechanism [25]. Diseases of the eye, such as diabetes, tend to affect uniformly both RG and YB mechanisms, although the loss of YB sensitivity precedes RG in early stage age-related macular degeneration [26]. The prevalence of retinal and systemic diseases that affect vision increases with age and almost invariably these cause loss of chromatic sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have shown that color vision deteriorates with advancing age [23,24], some controversy remains as to whether normal aging affects more the YB mechanism [25]. Diseases of the eye, such as diabetes, tend to affect uniformly both RG and YB mechanisms, although the loss of YB sensitivity precedes RG in early stage age-related macular degeneration [26]. The prevalence of retinal and systemic diseases that affect vision increases with age and almost invariably these cause loss of chromatic sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Color vision deficiencies may be congenital or secondary to disease and often manifest as a decreased ability to differentiate between shades of a color or between two or more colors. Ocular conditions such as diabetic retinopathy (DR), age-related macular degeneration (AMD), and glaucoma are known to affect color vision prior to affecting visual acuity (VA) (Greenstein, Hood, Ritch, Steinberger, & Carr, 1989;O'Neill-Biba, Sivaprasad, Rodriguez-Carmona, Wolf, & Barbur, 2010). In individuals with diabetes mellitus (DM), color vision impairment has been documented to emerge in the early stages of the disease and may precede the development of DR (Feitosa-Santana et al, 2006;Kurtenbach, Schiefer, Neu, & Zrenner, 1999;.…”
Section: Introductionmentioning
confidence: 99%
“…Chromatic thresholds will be measured for the eye with early AMD using the Colour Assessment and Diagnosis test [48] (City Occupational Ltd). Contrast thresholds to a 14 Hz flickering stimulus will be measured for the eye with early AMD using the procedure outlined by Dimitrov et al [49].…”
Section: Methodsmentioning
confidence: 99%